Protective Effect of Kaempferol and Its Nanoparticles on 5-Fluorouracil-Induced Cardiotoxicity in Rats. (13th February 2022) - Safarpour, Soheila; Pirzadeh, Marzieh; Ebrahimpour, Anahita; Shirafkan, Fatemeh; Madani, Fateme; Hosseini, Mohammad; Moghadamnia, Ali Akbar; Kazemi, Sohrab
Abstract : Background . Fluorouracil (5-FU) is the third most common chemotherapeutic agent used in the treatment of solid tumors. 5-FU-associated cardiotoxicity ranks the second causes of cardiotoxicity induced by chemotherapeutic drugs after anthracyclines. Kaempferol (KPF), a common flavonoid, possessing anti-inflammatory, antiapoptotic, antioxidative properties, and its protective effects on cardiovascular disease has been reported in various studies. The current study is aimed at appraising the effect of KPF and KPF nanoparticles (NPs) on 5-FU-induced cardiotoxicity in rats. Methods . Thirty Male Wistar rats were divided into five groups as follows: control, 5-FU, 5-FU+10 mg/kg vitamin C, 5-FU+ 1 mg/kg KPF, and 5-FU+ 1 mg/kg KPF-NPs. Cardiotoxicity was induced with an intraperitoneal injection of a single dose of 5-FU (100 mg/kg). The control group received normal saline, and the treatment groups received KPF and KPF-NPs with an intraperitoneal injection for 14 days. Each heart histopathological lesions were given a score of 0 to 3 in compliance with the articles for statistical analysis. Results . 5-FU resulted in a significant cardiotoxicity represented by an increase in cardiac enzymes, MDA (malondialdehyde) levels, COX-2 (cyclooxygenase-2) expression, and histopathological degenerations. 5-FU treatment also decreased body weight, TAC (total antioxidant capacity) values, VEGF (vascular endothelial growth factor) expression, blood cells, and hemoglobin (Hb) levels. Treatment with KPF and KPF-NPs reduced oxidative stress, cardiac enzymes, COX-2 expression, and VEGF expression. The number of blood cells, Hb levels, and histopathological degenerations, in cardiac tissue also body weight of animals, increased, followed by treatment with KPF and KPF-NPs. Conclusion . Our results demonstrated that treatment with KPF and KPF-NPs significantly improved cardiotoxicity induced by 5-FU in rats.